Multidimensional Property Supplementation: A Method for Discovering and Describing Emergent Qualities of Concepts in Grounded Theory Research. (January 2021) - Johnsson, Linus
Multidimensional property supplementation is a grounded theory method for analysis that conceives of concepts as multidimensional spaces of possibilities. It is applied in an iterative process comprising four steps: expansion, whereby vague codes are split and contraries postulated; abstraction of practically significant differences in terms of properties and dimensions; geometrization of properties to create conceptual subspaces that supplant subcategories and have additional, emergent qualities; and unification of the concept by validating it against data and relieving it of properties that do not tie in sufficiently with other concepts. Multidimensional conceptual models encourage the researcher to elaborate properties that explain, predict, or guide action. Fully developed, they can be easily connected to others in a process and function, by virtue of their emergent qualities, as falsifiable hypotheses in their own right. For these reasons, multidimensional property supplementation is open to epistemological justification without presuming acceptance of techniques specific to grounded theory.